Service Design Performance Based On Consumer Preferences : Case Study In Nav Karaoke Family Biliton In Surabaya City - Enny Istanti; Achmad Daengs GS; Rina Dewi; Diana Zuhro; Sutini Sutini; Moch. Rizaldy Rahmansyah (International Journal of Economics and Management Sciences, 2024)
In order to have strong competitiveness in an environment that continues to move dynamically, a business entity such as NAV Karaoke needs to think about a superior service package that has high competitiveness and is a favorite service that consumers want. In creating a NAV karaoke service or product package, it is necessary to think about a design that truly reflects the consumer's desires for karaoke entertainment products. Starting from the need to create a karaoke service design sourced from consumers, the researcher intends to empirically study what product or service items are like regarding the quality of service provided by PT. NAV Karaoke Family Biliton Surabaya, from this research it is hoped that it will be possible to find out how the public perceives existing services and how to improve them. Consumer preferences can literally be interpreted as the behavior shown by consumers in searching for, selecting, buying, using, evaluating the quality of business products and services that can satisfy their needs (based on a value system / experience / customer value). Consumer preferences for the attributes of a product are the level of suitability of the attributes of the product or service with consumer needs. The main factor necessary to know and understand value is to be truly aware of the needs of individual consumers and the market segments in which they are concerned. Service design is the value contained in a service and in the form of a service appearance that is distinctive and attractive and differentiates it from competing services, where service design can produce its own allure that attracts consumers' buying interest.